Community-based mental health interventions in low- and middle-income countries: a qualitative study with international experts - Clarissa Giebel; Mark Gabbay; Nipun Shrestha; Gabriel Saldarriaga; Siobhan Reilly; Ross White; Ginger Liu; Dawn Allen; Maria Isabel Zuluaga (BMC, 2024)
Abstract Background Mental health services are scarce in low- and middle-income countries (LMICs), and designing and implementing effective interventions can be difficult. The aim of this international study was to explore the key lessons for developing, implementing, and evaluating community-based mental health and well-being interventions in LMICs, with an additional focus on older adults. Methods Research and clinical experts in developing and implementing psychosocial community-based interventions in LMICs were interviewed remotely between October 2021 and January 2022. Participants were recruited via existing global health networks and via published literature searches. Participants were asked about their experiences of developing and implementing interventions, and about key barriers and facilitators during the process. Interviews lasted up to 45 min, and data were analysed using combined inductive and deductive thematic analysis. Results Sixteen global mental health experts participated. Five themes with different sub-themes were generated: Mechanisms and contexts; Barriers; Facilitators; Public and stakeholder involvement; Looking through an ageing lens. The development and delivery of mental health interventions in LMICs are facilitated through integration into existing health infrastructures and working with existing job roles as delivery agents. Public and stakeholder involvement are crucial at all stages of development through to implementation to focus on meeting local needs and sustaining participant motivation. Logistical barriers of transport, resources, and location need to be addressed, emphasising local sustainability. Conclusions This study provides important insights for how the development, implementation, and evaluation of community-based mental health and well-being interventions in LMICs can be optimised, and can complement general guidance into complex interventions developments.